Palladium‐Catalyzed Direct Oxidative Coupling of Iodoarenes with Primary Alcohols Leading to Ketones: Application to the Synthesis of Benzofuranones and Indenones. Issue 30 (18th July 2019) - Suchand, Basuli; Sreenivasulu, Chinnabattigalla; Satyanarayana, Gedu
Abstract : In the present study, a palladium‐catalyzed direct oxidative acylation through cross‐dehydrogenative coupling has been investigated, utilizing readily available primary alcohols as acylating sources. Overall, this oxidative coupling proceeds via three distinct transformations such as oxidation, radical formation, and cross‐coupling in one catalytic process. This protocol does not involve the assistance of a directing group or activation of the carbonyl group by any other means. Furthermore, this reaction made use of no toxic CO gas as carbonylating agent; instead, feedstock primary alcohols have been utilized as acylation source. Notably, the synthesis of benzofuranones and indenones is enabled. This strategy was also applied to the synthesis of n ‐butylphthalide, fenofibrate, pitofenone, and neo‐lignan. Abstract : Palladium‐catalyzed direct oxidative acylation through cross‐dehydrogenative coupling has been demonstrated, for the synthesis of a wide varity of ketones. Readily available primary alcohols have been utilized as acylating sources. Overall, this oxidative coupling proceeds via three distinct transformations such as oxidation, radical formation and cross‐coupling in one catalytic process.